New possibilities for lipid level control using inclisiran — prospects for interaction between a cardiologist and a neurologist - A. B. Skiba; M. V. Menzorov; V. D. Puchek; I. M. Buchin; I. I. Polyakov; E. N. Menzorova (Рациональная фармакотерапия в кардиологии)
Dyslipidemia is one of the most significant modifiable cardiovascular risk factors. The change in the modern paradigm for dyslipidemia treatment from high-intensity statin therapy to high-intensity lipid-lowering therapy makes it possible to more often use new drug classes to achieve the target level of low-density lipoprotein cholesterol. The article presents two case reports on the use of inclisiran as part of combination lipid-lowering therapy for secondary prevention in patients at very high cardiovascular risk. Based on the presented cases, following clinical aspects of the management of cardiovascular patients are discussed: the safety of achieving low-density lipoprotein cholesterol levels below 1 mmol/l in a patient with asymptomatic cerebral infarction, the need for adequate dyslipidemia treatment after revascularization, the strategic importance of prescribing lipid-lowering therapy in patients with cerebrovascular disease to reduce the cardiovascular risk, adherence to therapy as a significant aspect of effective dyslipidemia control.